Evaluation of Blast Disease Resistance in Rice Plants (Oryza sativa) Resulting from BSR-D1 Gene Editing Through In-Planta Transformation With CRISPR/Cas9 Technology - Muhammad Wajdi Hakimi; Wahyuni Umami; Rogayah Sekeli (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2026)
Rice blast disease, caused by the fungus Magnaporthe oryzae, poses a significant threat to rice productivityworldwide. To enhance rice resistance to this disease, CRISPR/Cas9 gene-editing technology has been used tomodify the Bsr-d1 gene, which is known to regulate plant resistance to fungal infections negatively. This studyaims to evaluate the blast disease resistance of the T2 generation of the Bsr-d1 gene-edited rice variety MR 297.The transformed plants were inoculated with a P. oryzae isolate (Isolate MR297 3.1), and disease symptoms wereassessed nine days post-inoculation using the IRRI scale (0–9). The results demonstrated that several gene-editedplant lines exhibited significantly milder disease symptoms compared to susceptible control plants. These findingsindicate that editing the Bsr-d1 gene effectively enhances rice resistance to blast disease without compromisingkey agronomic traits. By eliminating the need for tissue culture, this protocol offers a simpler and more efficientapproach with the potential for widespread adoption in disease-resistant rice breeding programs. The primaryadvantage of this study is the application of CRISPR/Cas9 technology to specifically target the Bsr-d1 gene, anegative regulator of blast resistance. This method enhances rice plant resistance without introducing foreigngenes, increasing its likelihood of regulatory approval and acceptance in field applications. Resistance testingusing local isolates of Magnaporthe oryzae enhances the relevance of the findings to local agroecosystemconditions. Furthermore, the study demonstrates that increased resistance does not compromise key agronomictraits, supporting the development of superior rice varieties that are both high-yielding and disease-resistant. It isrecommended that users conduct multi-location and multi-season trials to evaluate the stability of gene-editedplant resistance under varying environmental conditions and pathogen pressures. Additionally, a more in-depthanalysis of the impact of the Bsr-d1 gene on the expression of other genes related to plant growth and yield isnecessary.